Influence of injection angles on flow structures and mixing properties in a supersonic combustor at low Mach supersonic crossflow - Lin Zhang; Jianhan Liang; Yi Wang; Wei Zhao; Leichao Yang (Scientific Reports)
Abstract The fuel-air mixing is of paramount importance in hypersonic air-breathing vehicles, and its performance is closely related to the fuel injection angle. This article presents an investigation into the influence of the injection angles on the flow and mixing processes in a supersonic combustor at low Mach supersonic inflow. Detailed flow characteristics are compared and analyzed, with a focus on instantaneous and average flows. Besides, several significant mixing parameters are thoroughly depicted. Results show that, in contrast to transverse injection, relatively strong fuel fluctuation is presented on the leeward side in comparison to the windward side in the near field for the inclined injection. Furthermore, the counter-rotating vortex pairs (CVP) are constricted by the inclination of the injection, giving rise to a decrease in jet-cavity interaction. Although inclined injection exhibits favorable performance in backpressure resistance at low Mach supersonic crossflow, it presents a greater challenge in terms of ignition, thus necessitating meticulous design considerations.